Aerospace 2004
DOI: 10.1115/imece2004-60556
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Loading Behaviour of Auxetic Thermoplastic Foams

Abstract: The paper describes the manufacturing and tensile testing of auxetic (negative Poisson’s ratio) thermoplastic polyurethane foams. The foams are produced from conventional flexible polyurethane basis following a manufacturing route developed in previous works. The Poisson’s ratio behavior over tensile strain has been analyzed using an Image Data processing technique based on Edge Detection from digital images recorded during quasi-static tensile test. The samples have been subjected to tensile and compressive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This new method was more versatile than the previously established three‐stage processing route. Scarpa and Pastorino [ 12 ] performed a quasi‐static compression test on the conventional and auxetic foam, and showed that the stress–strain diagram of auxetic foam is very different with that of the conventional polyurethane foam. This research provided a model for detecting the cell failure behavior of auxetic foam since the sides of the cell were bent.…”
Section: Introductionmentioning
confidence: 99%
“…This new method was more versatile than the previously established three‐stage processing route. Scarpa and Pastorino [ 12 ] performed a quasi‐static compression test on the conventional and auxetic foam, and showed that the stress–strain diagram of auxetic foam is very different with that of the conventional polyurethane foam. This research provided a model for detecting the cell failure behavior of auxetic foam since the sides of the cell were bent.…”
Section: Introductionmentioning
confidence: 99%